Pengetahuan Lansia Terhadap Pencegahan Kekambuhan Hipertansi: Literatur Review: Pengetahuan Lansia Terhadap Pencegahan Kekambuhan Hipertansi: Literatur Review - Saputro, Gilang; Haerani , Mia; Balqis, Ummi Malikal; Haerani, Mia (Jurnal Kesehatan Masa Depan, 2024)
Introduction: A person aged sixty years and above is considered elderly. The aging process will naturally occur in individuals within this age group. As a result of the degenerative processes associated with aging, most elderly people experience a decline in physiological functions, making them more vulnerable to various diseases, including hypertension. Hypertension, a disease that affects the blood vessels, can hinder the delivery of oxygen and nutrients to body tissues. Research objective: to find out how the knowledge of the elderly affects the prevention of recurrent hypertension. Method: A literature review of several selected articles was used in this research. Regarding the knowledge of elderly people in preventing hypertension recurrence, participants expressed two themes, namely knowledge influences hypertension recurrence and quality of life influences hypertension recurrence. For those suffering from hypertension, in order to manage their blood pressure effectively and prevent recurrence of this disease, knowledge and a good quality of life regarding this condition is very important.